The Muslim Scholars and the History of Economics: A Need for Consideration (American Journal of Islam and Society, 1987)
Introduction. . .The enterpriser addressing a Greek who had been boasting of the scientificachievement of his people, says: You boast most unreasonably of these sciences;for you did not discover them by your own penetration, but attained them fromthe scientific men of Ptolemy's times; and some sciences you took from the Eygptiansin the days of Prammetichus, and then introduced them into your ownland, and now you claim to have discovered them. The King asked the Greekphilosopher: "Can it be as he says?" He replied saying, "It is true; we obtainedmost of the sciences from the preceding philosophers, as others now receivethem from us. Such is the way of the world - for one people to derive benefitfrom another. Rasail of the Ikhwan Al-SafaNever in any age was any science discovered, but from the beginning of theworld wisdom has increased gradually, and it has not yet been completed asregards this life. Roger Bacon. . .there is no longer any excuse for a pmctice which has confounded the studyof medieval economics since its inception more than a century ago, namely,that of basing the most sweeping historical generalizations on a fav familiarnames, with no regard for context and continuity; even the best textbooks inthe field still skip and jump from one century to the next, in and out of differenttraditions. But a scholastic commentator superimposed his own ideas on thoseaccumulated in the particular tmdition in which he wrote, accepted its premisesand adopted its language. He cannot be fully understood until its foundationis also dug out.It is easy now to forget that those who laid the foundation of modemeconomics in the eighteenth century were as familiar with the accumulated ...